Transitioning to a green economy in Greece - Leidecker, Timo (OECD Economics Department Working Papers, 2023)
A changing climate is threatening livelihoods and economic activity in Greece and the world. Transitioning to a green economy - mitigating the causes of climate change and adapting to its effects, while sustaining activity and improving well-being - is among the greatest policy challenges of the coming decades. In Greece, legacies of high emission intensity, limited fiscal space and scarce private financing amplify the challenge. Greening Greece's energy system is at the core of this transition. This entails swiftly developing its large potential for renewable energies and adapting energy consuming sectors. A well-chosen mix of policies - including carbon pricing, public infrastructure investments, and gradually tightening regulations on minimum energy efficiency standards, while providing financial support and protecting vulnerable households - would minimise the cost of this transition. Developing insurance coverage can better protect households and firms from damages resulting from a warming climate, while limiting fiscal exposure. Engaging all stakeholders and supporting those affected by the transition will help build the consensus for implementing these policies into the long-term